E3 Ubiquitin Ligases: Key Regulators of Hormone Signaling in Plants - Kelley, Dior R. (Mol Cell Proteomics, 2018)
Ubiquitin-mediated control of protein stability is central to most aspects of plant hormone signaling. Attachment of ubiquitin to target proteins occurs via an enzymatic cascade with the final step being catalyzed by a family of enzymes known as E3 ubiquitin ligases, which have been classified based on their protein domains and structures. Although E3 ubiquitin ligases are conserved among eukaryotes, in plants they are well-known to fulfill unique roles as central regulators of phytohormone signaling, including hormone perception and regulation of hormone biosynthesis. This review will highlight up-to-date findings that have refined well-known E3 ligase-substrate interactions and defined novel E3 ligase substrates that mediate numerous hormone signaling pathways. Additionally, examples of how particular E3 ligases may mediate hormone crosstalk will be discussed as an emerging theme. Looking forward, promising experimental approaches and methods that will provide deeper mechanistic insight into the roles of E3 ubiquitin ligases in plants will be considered.